Circunstância, Memória e Método. Uma experieência de projecto. - Pedro Xavier Barbosa Oliveira (2014)
This theoretical presentation is based on developing of a practical architectural design. The most important part of the proposal aims the design a new building for the company's footwear Oliveira &Santos Lda., and for that reason we are confronted, for the first time, with a real design project, with a real client and moreover with real problems. In what concerns this work, we intend to reflect about the best method to develop new ideas, specially, about the principles and influences that shape the choices made at the time to think about the proposal. First, the design is marked by the value given to the circumstances which surrounds the project, not only the ones that previously determine the place and the programme, but also those that arise throughout their development. From our point of view we want that, the final form, is the result of an exhaustive search for the best response to the set of constraints involved in the design process. A personal view of the organizer is the most important component in the formulation of ideas. There is a complex set of assimilated references into our memory that influence our way of thinking, even when we have to deal with concrete and precise constraints. The essential idea, which structures the project and defines its basic concept, comes not only from the architect but also from factors such as his / her own personality. As far as our own idea is concerned, we recognize two basic elements: the Masters teaching and the architecture models. On the one hand, a Master teaches according with his / her principles. Their teachings are transmitted through his/ her theoretical or practical work, and from that we can understand his / her own point of view about the architecture, looking for answers in which we can solve our project problems. On the other hand, their models inspire us, we want to know exactly how they are made and their characteristics to apply to our own work. It is from these elements that we develop the presented theoretical reflection, applying the principles stated in a simultaneous exposition of the design process.